2019
DOI: 10.3390/cancers11040559
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Implication of Epigenetic Alterations in the EMT of Triple Negative Breast Cancer

Abstract: Breast cancer is the most common cancer and leading cause of cancer death among women worldwide, encompassing a wide heterogeneity of subtypes with different clinical features. During the last two decades, the use of targeted therapies has emerged in clinical research in order to increase treatment efficiency, improve prognosis and reduce recurrence. However, the triple negative breast cancer (TNBC) subtype remains a clinical challenge, with poor prognosis since no therapeutic targets have been identified. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 130 publications
1
68
0
Order By: Relevance
“…miRNAs could suppress gene expression at both transcriptional and posttranscriptional level by binding to complementary sequences of its target mRNA 17 . miRNAs serve as a crucial components in epigenetic modification for many important biological pathways including EMT 18 . Previous research has suggested that miR-337-3p could regulate the EMT process during cancer progression and metastasis 19 .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs could suppress gene expression at both transcriptional and posttranscriptional level by binding to complementary sequences of its target mRNA 17 . miRNAs serve as a crucial components in epigenetic modification for many important biological pathways including EMT 18 . Previous research has suggested that miR-337-3p could regulate the EMT process during cancer progression and metastasis 19 .…”
Section: Introductionmentioning
confidence: 99%
“…EMT is defined as the loss of epithelial phenotypes and the gain of mesenchymal characteristics [5]. These changes endow cancer cells with higher metastatic capacity and contribute to abnormal cellular growth, differentiation and drug resistance [6]. Some signaling pathways are previously reported to be involved in EMT, such as transforming growth factor-β (TGF-β), cadherin, Notch, Wnt/β-catenin, and GATA [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common type of malignancy in women and is the second leading cause of female cancer mortality in the world [1][2][3]. Recent reports have revealed that breast cancer is responsible for 6% of the total 7.5 million cancer mortalities worldwide [3,4]. Although numerous advanced diagnostic and therapeutic methods have been used in the treatment of breast cancer, but its metastasis is still the primary cause of death [5,6].…”
Section: Introductionmentioning
confidence: 99%